The MSMEs Decision To Publish The Prospectus: A Case Study On Funding In Ammana Fintech - Tri Wahyu Oktavendi (Jurnal ASET (Akuntansi Riset), 2022)
The objective of this study is to understand factors that affect on the MSMESs decision to publish the prospectus. The data in this study are secondary data, in the form of Prospectus Data, Total Funds, Funding Status, and Profit Sharing Percentages. All of this data can be found on the I-Fintech website: Ammana. The sample used in this study were 337 Funding. This study uses logistic regression with the help of the STATA 15 analysis tool. The results showed that the Financing Value and Applicant Status have an influence on Prospectus Publishing. This means that the greater the Financing Value and the Applicant Status Repeating the possibility of MSMEs to publish the Prospectus in filing crowdfunding funds at I-Fintech (Ammana Fintech).